Outcomes of the surgical management of encapsulating peritoneal sclerosis: A case series from a single center in Korea - Jung-Hwa Ryu; Kil-Yong Lee; Tai Yeon Koo; Dong Ki Kim; Kook-Hwan Oh; Jaeseok Yang; Kyu Joo Park (The Korean Society of Nephrology, 2019)
Background : Encapsulating peritoneal sclerosis (EPS) is a rare but near-fatal complication of peritoneal dialysis (PD). Despite the high mortality rate of EPS, the surgical treatment strategy of severe EPS is yet to be established.Methods : We retrospectively analyzed outcomes of patients with EPS who underwent enterolysis for intractable EPS at Seoul National University Hospital between 2001 and 2018. EPS was diagnosed based on the clinical symptoms and radiological findings of abdominal computed tomography (CT). CT scans were scored according to an EPS scoring system that assessed peritoneal thickening and calcification as well as bowel thickening, tethering, loculation, and dilatation.Results : Thirteen patients (nine males and four females; age, 48 [29-63] years) underwent enterolysis for severe EPS. PD duration (11 [6-21] years) was not associated with survival. Two patients were newly diagnosed with EPS following kidney transplantation. Five patients died of infectious complications immediately after the surgery. Eight patients survived after the first surgery; however, five of them underwent reoperation but died of persistent infection, fistula formation, or adhesive bowel obstruction. Four young (< 60 years) male patients with relatively low CT scan scores (< 13) survived for > 2 years after the first surgery. Median survival duration from EPS diagnosis was 22 (1.3-184) months and that from the first surgery was 9 (0.3-153) months.Conclusion : The high mortality rate of EPS suggests the importance of appropriate surgical intervention in young symptomatic male EPS patients with relatively low CT scan scores.